Analisis Kebijakan Pemerintah dalam Pengembangan UMKM melalui Platform Crowdfunding - Friska Amelia; Imsar Imsar; Muhammad Ikhsan Harahap (Universitas 45 Surabaya, 2025)
This article analyzes the role of government policy in supporting the development of Micro, Small, and Medium Enterprises (MSMEs) through crowdfunding platforms in Indonesia. Crowdfunding is increasingly being seen as an innovative and accessible funding alternative, especially for MSMEs facing capital constraints. The research uses a qualitative descriptive method by reviewing government policies and regulatory frameworks as well as existing crowdfunding practices. The findings indicate that the effectiveness of crowdfunding for MSMEs relies on policy clarity, digital literacy, and synergy between the government, platform providers, and business actors. The study emphasizes the importance of a sharia-compliant funding framework to enhance trust and participation, particularly given the regulatory gaps and the dominance of non-sharia platforms. This research underscores the necessity of adaptive government policies, targeted digital literacy programs (especially in regions like North Sumatra/Medan), and the formalization of sharia crowdfunding models to achieve financial inclusion and sustainable economic empowerment for MSMEs